Pendidikan Karakter Melalui Program Tujuh Kebiasaan Anak-Anak Hebat Indonesia untuk Anak Usia Dini - Anada Leo Virganta; May Sari Lubis; Nur Qomariah Panjaitan (Jurnal Tematik, 2026)
The implementation of the digital media-based song "Tujuh Sifat Anak-Anak Hebat Indonesia" in Medan certainly faces challenges and obstacles, both in terms of the availability of technological facilities and teachers' readiness to use the song in early childhood learning. Based on field observations, not all early childhood education institutions in Medan have adequate access to technological devices and the internet. Furthermore, many early childhood education teachers still have difficulty accessing information using the internet and other digital technologies. These limitations hinder the optimal use of digital media in learning. Some early childhood education institutions in Medan pay little attention to arts learning activities, including music. This results in a lack of creativity in children and limited use of digital media in music teaching. The purpose of this study was to determine the implementation strategy for the digital media-based song "Tujuh Sifat Anak-Anak Hebat Indonesia" and its implications for positive character development in early childhood. The research method used was descriptive qualitative, using observation, interviews, and document study techniques.